Spectrophotometric Determination of Pravastatin Sodium in Pharmaceutical Oral Solid Dosage Forms - Kalvikkarasi, S.; Vaidhyalingam, V.; Niraimathi, V.; Aruna, Ajithadas (Asian Journal of Chemistry, 2010)
Two simple, sensitive and reproducible spectrophotometric methods (methods A and B) were developed for estimation of pravastatin sodium in pure as well as in pharmaceutical formulations. Method A is based on the reduction of ferric to ferrous ions followed by complexation with 2,2'-bipyridyl to produce an orange red chromogen at λmax of 522 nm and method B is based on the reduction of ferric to ferrous ions followed by complexation with 1,10-phenanthroline to produce an orange red chromogen at λmax of 510 nm and both obeyed Beer’s linearity in the concentration range of 50-250 μg/mL for method A and 20-100 μg/mL for method B. These methods were extended to pharmaceutical formulations.